Customer responses to produce at point of sale in lighting simulations - Nandy, Barnali (Kansas State University, 2003)
The study focuses on relationships between lighting simulated using computer graphics and subject responses with the intent of determining aspects of lighting that would affect the consumers while shopping for produce. The research design included presentation of computer simulations of lighting in a retail space to the subjects. The simulations were modeled based on the typical environment of a produce section in a food market and were made to vary in their "quality" of lighting for the study. The quality of lighting depended on single or combination of factors such as illuminance, color of the lamp source, distribution of light and luminance ratios. The computer models were executed using Autodesk Viz 4. The subjects rated the simulations on six five -point rating scales as well as a direct question. These scales were based on the categories of impressions namely, perceptual clarity, behavioral impression and overall preference. The analysis of the responses showed that higher illuminance levels, higher luminance ratios and higher color temperature independently helped improving the visual clarity of the scene. However, low illuminance levels were more conducive to a "relaxing" environment. Accent lighting was preferred over an interior with no accent lighting. Such information tell the lighting designers of retail spaces that using accent lighting for focusing on the merchandise will help in attracting the customers, as long as the illuminance levels are not too high to make the customers feel uneasy in the environment. Selecting lamps with good color properties can make a difference in the appearance of the merchandise. The findings of the research also suggested that more evaluation was needed to measure perceptual clarity, mainly with respect to the effects of the source color. The computer generated models prepared in Autodesk Viz 4 were found to be not as effective in representing the combined effects of color temperature and illuminance or evoking the impression of relaxing vs. tense. This and similar research can help improve lighting design in the produce departments of food markets from the people's end and will also have the potential to be transferred to other retail environments, theaters and museums where the effects of lighting are also crucial.
Department: Architecture.